Level of burnout among nurses working in Public Health — Preliminary Study - Cipora, Elżbieta; Smoleń, Ewa; Gazdowicz, Lucyna; Maliwiecka, Teresa; Poźniak, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Background. Work can be a burden for nurses and the reason for burnout. There are many different definitions of burnout, but their common feature is the presence of negative symptoms of sickness resulting from the nature of professional tasks. Aim. Key objective of the studies was to determine the level of burnout in a nurses working group. Material and methods. Studies included 128 nurses working in health care institutions in the province of podkarpacie. Tools in research were: Questionnaire burnout Maslach and questionnaire containing questions about demographic, social and professional nurse. Results and conclusions. Among the nurses surveyed stated low degree burnout. The smallest burnout occurred in depersonalization. Higher degree of burnout was found in terms of emotional exhaustion and professional failure. Age of surveyed nurses, material status, place of residence, level of education, workplace did not differentiate significantly wear indicator overall level of burnout and individual dimensions of burnout. The vast majority of respondents declaring satisfaction within the occupation, was caused by the low levels of occupational burnout. Although the surveyed nurses declared satisfaction within the occupation, they still recieved symptoms of occupational burnout.